A review of urban development of Besiktas-Yildiz from the 19th century to the present - Bindal, Dilşat Deniz (ISEC Press, 2021)
The Besiktas district located in the Bogazici side of Istanbul experienced various changes throughout history. Considering these changes, there were no settlements in this district in ancient times. The district hosted three important structures in the Byzantine period and developed the identity of a settlement during the Ottoman Period. Besiktas became a region where palaces and pavilions were located and noble families and officers lived during the reign of Suleyman the Magnificent. As Sultan Abdulhamid the Second moved into Yıldız Palace, the district became the administrative region of the Ottomans. Therefore, the district experienced various urban changes and hosted many innovations. The region having historical and cultural values keeps its importance until today. The aim of the present study is to reveal the physical changes in the Besiktas-Yıldız region throughout history according to the requirements, cultural structural changes and regulations. Accordingly, the assessment section was addressed in three sections; until 19th century, during 19th century and after 19th century. The relevant literature was reviewed to determine the changing sociocultural and socio-economic structure of the region in stated period. The analyses of the physical changes were presented on maps and figures of that period. In the conclusion section, the factors that caused the changes were addressed. © 2021 ISEC Press.
Keywords: capital of ottoman; palaces of ottoman; physical change in cities; the influence of the palace on the city in ottoman